Effectiveness of a multidisciplinary care program on recovery and return to work of patients after gynaecological surgery; design of a randomized controlled trial - Vonk Noordegraaf Antonie; Huirne Judith AF; Brölmann Hans AM; Emanuel Mark H; van Kesteren Paul JM; Kleiverda Gunilla; Lips Jos P; Mozes Alexander; Thurkow Andreas L; van Mechelen Willem; Anema Johannes R (BMC, 2012)
Abstract Background Return to work after gynaecological surgery takes much longer than expected, irrespective of the level of invasiveness. In order to empower patients in recovery and return to work, a multidisciplinary care program consisting of an e-health intervention and integrated care management including participatory workplace intervention was developed. Methods/Design We designed a randomized controlled trial to assess the effect of the multidisciplinary care program on full sustainable return to work in patients after gynaecological surgery, compared to usual clinical care. Two hundred twelve women (18-65 years old) undergoing hysterectomy and/or laparoscopic adnexal surgery on benign indication in one of the 7 participating (university) hospitals in the Netherlands are expected to take part in this study at baseline. The primary outcome measure is sick leave duration until full sustainable return to work and is measured by a monthly calendar of sickness absence during 26 weeks after surgery. Secondary outcome measures are the effect of the care program on general recovery, quality of life, pain intensity and complications, and are assessed using questionnaires at baseline, 2, 6, 12 and 26 weeks after surgery. Discussion The discrepancy between expected physical recovery and actual return to work after gynaecological surgery contributes to the relevance of this study. There is strong evidence that long periods of sick leave can result in work disability, poorer general health and increased risk of mental health problems. We expect that this multidisciplinary care program will improve peri-operative care, contribute to a faster return to work of patients after gynaecological surgery and, as a consequence, will reduce societal costs considerably. Trial registration Netherlands Trial Register (NTR): NTR2087